Photo- and acid induced multicolor switches based on pyridine-containing perfluorodiarylethene derivatives. Issue 15 (14th April 2016) - Zheng, Chunhong; Liu, Hongliang; Fan, Congbin; Pu, Shouzhi
Abstract: Two novel perfluorodiarylethenes which contains a 2-methylbenzo[b]furane and a modified pyridine moiety were synthesized. Such structure may induce F⋯N or S⋯N heteroatom contact which was newly observed. Experiments results showed that the photocyclization quantum yield exhibited a strong correlation with the two weak intramolecular interactions, which behaved solvent independency. Moreover, both novel pyridine-perfluorodiarylethenes exhibited an obvious acidichromism, and the absorption maxima of their closed-ring isomers showed a prominent bathochromic shift to the near-infrared region. Graphical abstract: